Analisis Wilayah dan Kontribusi Kakao Terhadap Pembangunan Daerah di Kabupaten Gunung Kidul - H, Nurlina; Millaty, Marosimy; Pratama, Mauladi (Universitas Galuh, 2024)
Economic and regional development cannot be separated from economic growth, where economic development will have an impact on economic growth and the continuation of regional development. This study aims to analyze the area and contribution of cocoa production to regional development in Gunung Kidul district, Yogyakarta. The research method used is location quotient (LQ) analysis. LQ analysis is a general approach that is often used as a first step to find out the economic base that triggers economic growth. The results obtained in research on cocoa production in Gunung Kidul district are that there are six sub-districts which are the basis for cocoa production centers in Gunung Kidul district. The six districts that are cocoa producers are Ponjong, Karangmojo, Playen, Patuk, Gedangsari, and Nglipar. Based on the results of the analysis, there are three (3) districts with an average LQ value of <1, and three (3) districts with an average value of LQ>1 in Gunung Kidul using the LQ method. Thus, cocoa's contribution to economic development in Gunung Kidul will always have a fluctuating but active value. However, the economic development of development in Gunung Kidul, especially in the agribusiness sector continues to experience a significant increase from year to year.